Dietary Magnesium Intake Level Modifies the Association Between Vitamin D and Insulin Resistance: A Large Cross-Sectional Analysis of American Adults - Liu, Ya; Gong, Rongpeng; Ma, Haixiu; Chen, Siai; Sun, Jingwei; Qi, Jiarui; Pang, Yidan; An, Juan; Su, Zhanhai (Frontiers in Nutrition, 2022)
Abstract Background: Previous clinical studies and randomized controlled trials have revealed that low serum vitamin D levels are associated with the risk of developing insulin resistance. Magnesium has been reported to be a protective factor for insulin resistance, and magnesium has been considered an important co-factor for vitamin D activation. However, the effect of dietary magnesium intake on the relationship between vitamin D and the risk of developing insulin resistance has not been comprehensively investigated. Therefore, we designed this cross-sectional analysis to assess whether dietary magnesium intake modifies the association of vitamin D and insulin resistance. Methods: A total of 4,878 participants (male: 48.2%) from 4 consecutive cycles of the National Health and Nutrition Examination Survey (2007–2014) were included in this study after a rigorous screening process. Participants were stratified by their dietary magnesium intake into low-intake (<267 mg/day) and high-intake (≥267 mg/day) groups. We assessed differences between serum vitamin D levels and the risk of developing insulin resistance (interaction test), using a weighted multivariate logistic regression to analyze differences between participants with low and high magnesium intake levels. Results: There was a negative association between vitamin D and insulin resistance in the US adult population (OR: 0.93 (0.88-0.98)), P<0.001. Dietary magnesium intake strengthened the association (P for interaction < 0.001). In the low dietary magnesium intake group, vitamin D was negatively associated with the insulin resistance (OR: 0.94 (0.90-0.98)); in the high dietary magnesium intake group, vitamin D was negatively associated with insulin resistance (OR: 0.92 (0.88-0.96)). Conclusion: Among adults in the United States, we found an independent association between vitamin D level and insulin resistance, and this association was modified according to different levels of magnesium intake. Keywords: vitamin D, cross-sectional studies, dietary magnesium intake, insulin resistance, nutrition